Modern challenges in improving business processes of digital organisation of enterprise structure in construction industry - N. V. Vozgoment (Вестник университета)
The current article analyses general problems of the processes of introducing BIM-technologies (building information model) in the construction industry of developing countries. The impact of the concept of scientific and technical progress on the development of information modelling in construction has been determined. The impact of introducing information BIM-technologies into construction processes at various stages of building an investment project is reflected – from development and design to commissioning, subsequent use and, if necessary, demolition of the object. The arguments justifying the need to develop BIM-modeling in investment processes of construction and design are presented. The modern interpretation of the concept of information modelling in the construction industry of developing countries is given. The author has described the main activities contributing to the development of the progress of implementing BIM-technologies in construction and domestic business in general. The goals and objectives of the digitalisation of the economy, including in construction, are considered and systematised. Also, the article discuses functions of design in construction, perspective variations of improving the quality of construction objects and reducing the level of risks and costs of the project.